Efeito de diferentes culturas láticas nas características de queijo tipo petit suisse com retenção de soro - Oliveira, Raquel França de (2015)
In order to contribute to reducing the whey generation during the production process of petit suisse cheese, the total use of nutrients contained in milk and increase manufacturing yield, this study was carried out aimed to evaluate the use of different lactic cultures in characteristics physical, physical-chemical, sensory and microstructural of petit suisse cheese with whey retention. The cultures used were R-704 composed by mesophilic bacteria, RST-744 composed by mesophilic and thermophilic bacteria, and CO-03 composed of thermophilic bacteria. First, it was evaluated the cheese’s fermentation time made from different cultures at temperatures of 32 °C, 37 °C, 40 °C and 43 °C, totaling nine treatments, being the control petit suisse cheese produced from the culture R-704 at temperature of 32 °C. Composition analysis were held one day after making cheeses, and water activity analysis, pH, acidity, syneresis and instrumental texture of the cheeses were carried out during 29 days of storage at the following periods: 1st day, 8th day, 15th day, 22 th day and 29 th day postmaking. The use of different cultures did not influence in the composition and cheese’s water activity. The cultures CO-03 and RST-744 provided to the cheeses higher acidity, syneresis, firmness, adhesiveness and gumminess, since the culture R-704 used in control provided to the cheese greater cohesiveness. Whey retention caused an increase in the cheese yield, but was not observed influence from the cultures used. To proceed with the sensory analysis and scanning electron microscopy were chosen the treatments R-704 (control), the treatment which used the culture RST-744 and fermentation temperature 37 °C (RST-744 37 °C) and the treatment which used the culture CO-03 at fermentation temperature 37 °C (CO-03 37 °C), because these treatments presented lower syneresis rates during the storage. In sensory analysis stage were raised attributes for petit suisse cheeses from the check-all-that-apply (CATA) methodology and performed acceptance testing with children, one day post making, being the cheeses presented good acceptance with scores between like slightly and really liked. Scanning electron microscopy analysis showed that the treatment CO-03 37°C showed more compact microstructure.